Influence of monoterpenes in biological activities of Nectandra megapotamica (Spreng.) mez essential oils - Danielli, Letícia Jacobi (2019)
Investigating the influence of seasonal variations on biological activities is important for pharmacological studies and metabolic engineering. Therefore, this study was conducted to determine the variation of the chemical composition of essential oils obtained from Nectandra megapotamica leaves, collected at different stages of plant development, as well as its influence on the biological activities. A total of 38 compounds were identified that accounted for 97–99.2% of the chemical composition of the oils. Major differences were observed in the monoterpenic fraction, representing 5.1% of the compounds identified in the productive rest phase to 37.1% in the blooming phase. Bicyclogermacrene and germacrene D were the predominant compounds identified in the oil of all collections. Furthermore, limonene, β-pinene, and spathulenol were identified predominantly in the samples of blooming and fruiting phases. The oils exhibited significant antichemotactic activity and different effects in scavenging the radical 2,2-diphenyl-1-picrylhydrazyl. Variations were also observed in the antifungal activity, with the minimum inhibitory concentrations ranging from 125 to 500 μg/mL. These results demonstrate the influence of monoterpenes, primarily limonene, α-pinene, and β-pinene, on the bioactivities of the oil. Studies investigating the variations in the chemical composition of essential oil may offer a strategy to produce a compound or a group of compounds of interest to industries with a specific pharmacological focus.